Does manager ability influence the classification of lease arrangements?. Issue 1 (15th January 2020) - Brooks, Marcus; Hairston, Stephanie; Harter, Charles
Abstract : Purpose: The purpose of this paper is to examine the influence of manager ability on a firm's choice of lease classification and the decision to capitalize vs lease firm-specific assets. Design/methodology/approach: The authors use regression analysis to examine the association between manager ability, lease classification and asset specificity. Findings: Using 31, 110 firm-year observations from 1998 to 2013, the authors find a significant positive relationship between manager ability and the decision to classify leases as operating. The authors also find that high-ability managers are more likely to capitalize, rather than lease, specialized firm-specific assets. Research limitations/implications: The results imply that manager ability influences the choice of lease classification, which provides some support for the recent changes to lease accounting in Accounting Standard Update (ASU) 2016-02. The authors also show that asset specificity may serve as a mitigating factor in high-ability managers' preference for operating leases, which implies that high-ability managers' concerns with operational efficiency outweigh the benefits of off-balance sheet financing in their purchasing decisions if the asset in question is firm-specific. Practical implications: The findings may be useful to boards of directors, investors and accounting academics concerned with the role that managerial ability plays in operational decision making and financial reporting. Originality/value: The results imply that high-ability managers prefer off-balance sheet financing, which is unlikely to limit their access to external capital, but that this relationship is mitigated if the firm requires highly specialized assets.